PENERAPAN MODEL PEMBELAJARAN INKURI UNTUK MENINGKATKAN PROSES PEMBELAJARAN IPA SISWA KELAS V SDN 033 SINTONG - Mistorina, Mistorina; Zulkifli, Zulkifli; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research study lack of public school students of class V 033 Sintong with average grade of 6.5 out of 24 students have not reached KKM 15 people (62.5%) while the achieve KKM only 9 people (37.9%). The formulation of this research is the implementation of inquiry learning model can improve learning outcomes fifth grade science students of SDN 033 Sintong? The purpose of this research is to improve science learning outcomes of students through inquiry learning model in class V SDN 033 Sintong. This study design is a Class Action Research (PTK). This research was conducted in two cycles, which is 4 times the material meeting 2 times daily tests. Instrument collecting data in this study is the observation sheet teachers and students as well as the achievement test. The activities of teachers in the first cycle and second cycle increases, in the first meeting of the first cycle of teacher activity percentage 66.67%, increased by 8.33 to 75% at the second meeting. At the third meeting increased by 12.5% to 87.5%. And at a meeting of the fourth increased by 4.17% to 91.67%. Increased activity of this teacher because of the improvement of the shortcomings in the previous meeting the learning process based on the results of reflections conducted at each meeting. Based on observations of student activity each meeting also increased. At the first meeting of the percentage of activity was 62.5% increased by 8.33% in the second meeting becomes 70.83%. at the third meeting rose as much as 8.33% to 83, 33% and in the fourth meeting rose as much as 8.34 5 to 91, 67%. Data from this study also experienced improve where prior to the act of inquiry learning model on the basis of the complete score of 9 (37.5 5) with an average of 65%, increasing the cycle 1 tuntas16 people (66.66%) with an average of 70 , 83% and on the second cycle increased the complete 21 people (87.5%) with an average of 82.9%. Improved overall learning outcomes 27, 53%. Based on these results it can be concluded that the implementation of inquiry learning model can improve learning outcomes fifth grade science students SDN 033 Sintong.Keyword : Inquiry Learning Model, learning outcomes IPA